Association of the female of Perdita (Xeromacrotera) cephalotes (Cresson), and a replacement name for Perdita bohartorum Parker (Hymenoptera: Andrenidae) - Portman, Zachary M.; Griswold, Terry; Pitts, James P. (Zootaxa, 2016)
The monotypic Perdita subgenus Xeromacrotera Timberlake is currently known only from the male sex. Here, the female of Perdita (Xeromacrotera) cephalotes (Cresson, 1878) is associated, resulting in two new junior synonyms of P. (X.) cephalotes: Perdita (Procockerellia) excellens Timberlake, 1958, new synonym and Perdita (Cockerellia) autumnalis Timberlake, 1977, new synonym. The true number of maxillary palpi are reported, and updated subgeneric and species diagnoses are provided. In addition, Perdita boharti Portman & Griswold, new name, is designated as a replacement name for the primary junior homonym P. bohartorum Parker, 1983 (not P. bohartorum Timberlake, 1956) and is assigned to the related subgenus Cockerellia Ashmead.